Comparative computational study of double rotating cylinder embedded on Selig S1223 aerofoil and flat plate for high altitude platform - Mohammad Ali, Hidayatullah; Mohd Rafie, Azmin Shakrine; Abdul Hamid, Mohd Faisal; Md Ali, Syaril Azrad (Universiti Putra Malaysia Press, 2022)
The high-altitude platform was built as an alternative approach to address the weakness of the terrestrial and satellite communication networks. It can be an aircraft or balloon positioned 20 to 50 km above the earth’s atmosphere. The use of the Magnus effect was not noticeable in the production of the high-altitude platform, while past research study has denoted its aerodynamic performance in generating greater lift and stall angle delay, which would be beneficial in creating such a flying device. This research delineates the proposed designs using the computational fluid dynamics approach utilizing ANSYS WORKBENCH 2019 software. The embedment of the rotating cylinder onto the design would best portray the use of the Magnus effect in generating higher lift coefficients with probable delay in stall angle. Hereby, the design of embedding rotating cylinder onto Selig S1223 aerofoil and the flat plate is proposed to test their aerodynamic performances for high altitude platform purposes. Here, Fluent fluid flow analysis was simulated for 500 RPM and 1000 RPM momentum injection with free stream velocities from 5 m/s to 30 m/s for different angles of attack of 0 to 20 degrees. The analysis has resulted in a greater impact on its lift coefficient and stall angle delay of about 39% and 53% enhancement for modified aerofoil while showing 128% and 204% betterment for modified flat plate than their respective unmodified model. Therefore, it is perceived that the CyFlaP has better stability yet is simplistic in a design suitable for HAP application.